2019
DOI: 10.1371/journal.pone.0216980
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects on the efficiency and responsiveness to phosphorus use in popcorn as estimated by diallel analysis

Abstract: Agricultural expansion and the need for sustainable cultivation are challenges faced by researchers involved in the generation of new cultivars that can adapt to abiotic stress. Knowledge of the genetic effects of characteristics related to efficiency and responsiveness to phosphorus use must be considered when implementing methods to obtain better genotypes. The aim of this study was to characterize and select popcorn hybrids based on their efficiency and responsiveness to phosphorus use, and estimate their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Regarding PE, the estimates of GCA effects on the P7 and L61 inbred lines showed that they were the most promising candidates, as the effects revealed the highest positive magnitudes of g i in both CSs and WCs. As PE is negatively correlated with GY, inbred lines with high GCA values for PE and low CGC values for GY or vice versa are commonly obtained (Cabral et al, 2016;de Lima et al, 2016;Mafra et al, 2018;Gerhardt et al, 2019) as we observed for L61. However, P7 had high values for both traits, which makes it of great importance for breeding programs when simultaneously exploring the potential for GY and PE.…”
Section: Combining Ability For Agronomic Traits Evaluated In Popcorn Under Wc In Each Cssupporting
confidence: 74%
See 2 more Smart Citations
“…Regarding PE, the estimates of GCA effects on the P7 and L61 inbred lines showed that they were the most promising candidates, as the effects revealed the highest positive magnitudes of g i in both CSs and WCs. As PE is negatively correlated with GY, inbred lines with high GCA values for PE and low CGC values for GY or vice versa are commonly obtained (Cabral et al, 2016;de Lima et al, 2016;Mafra et al, 2018;Gerhardt et al, 2019) as we observed for L61. However, P7 had high values for both traits, which makes it of great importance for breeding programs when simultaneously exploring the potential for GY and PE.…”
Section: Combining Ability For Agronomic Traits Evaluated In Popcorn Under Wc In Each Cssupporting
confidence: 74%
“…For maize under drought conditions, both non-additive (Derera et al, 2008 ; Adebayo et al, 2014 ) and additive effects were observed (Chapman and Edmeades, 1999 ; Betrán et al, 2003 ; Dhliwayo et al, 2009 ). The prevalence of the dominance effects for GY and additive effects for PE was observed in popcorn under soil nitrogen (N)-limited conditions (Santos et al, 2019 , 2020 ) and phosphorus (P)-limited conditions (Gerhardt et al, 2019 ). When evaluating popcorn genotypes under water-deficit conditions, Lima et al ( 2019 ) verified that dominance effects prevailed for GY while the same was true for additive effects for PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diallel crosses provide information about the genetic control of the traits evaluated, which helps in conducting and selecting segregating populations [6, 7]. The diallel also allows the breeder to know the per se behavior of the parents, called general combining ability (GCA), besides their hybrid combinations, called specific combining ability (SCA).…”
Section: Introductionmentioning
confidence: 99%
“…Griffing’s (1956) diallel analysis has used to uncover the behavior of genes involved in controlling of the traits. This method has also used to estimate variance of GCA and SCA in different self-pollinated and open-pollinated crops (Khan et al, 2009; Blank et al, 2012; Townsend et al, 2013; El-Gabry et al, 2014; Khodadadi et al, 2016b; Khodadadi et al, 2017; Kaushik et al, 2018; Teodoro et al, 2019; Schegoscheski Gerhardt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%